Percutaneous catheter drainage in combination with choledochoscope-guided debridement in treatment of peripancreatic infection - Tang, Li-Jun (The WJG Press and Baishideng, 2010)
AIM: To introduce and evaluate the new method used in treatment of pancreatic and peripancreatic infections secondary to severe acute pancreatitis (SAP). METHODS: A total of 42 SAP patients initially underwent ultrasound-guided percutaneous puncture and catheterization. An 8-Fr drainage catheter was used to drain the infected peripancreatic necrotic foci for 3-5 d. The sinus tract of the drainage catheter was expanded gradually with a skin expander, and the 8-Fr drainage catheter was replaced with a 22-Fr drainage tube after 7-10 d. Choledochoscope-guided debridement was performed repeatedly until the infected peripancreatic tissue was effectively removed through the drainage sinus tract. RESULTS: Among the 42 patients, the infected peripancreatic tissue or abscess was completely removed from 38 patients and elective cyst-jejunum anastomosis was performed in 4 patients due to formation of pancreatic pseudocysts. No death and complication occurred during the procedure. CONCLUSION: Percutaneous catheter drainage in combination with choledochoscope-guided debridement is a simple, safe and reliable treatment procedure for peripancreatic infections secondary to SAP.